Resiliensi Penggemar sebagai Strategi Komunikasi Krisis: Studi Kasus Fandom Kim Hyun-Joong Indonesia dalam Menghadapi Cancel Culture - Ratih Siti Aminah; Kandita Aulia Putri; Muslim Muslim; Yuyus Rustandi (Universitas Pakuan, 2026)
Cancel culture has evolved into a powerful social phenomenon that significantly threatens the image and career sustainability of figur publiks in the digital era. Kim Hyun-Joong, a South Korean artist, experienced this phenomenon through a prolonged legal controversy with his former girlfriend from 2014 to 2020. Despite the Supreme Court of South Korea ruling him not guilty in 2020, his public image continued to be affected by damaging narratives circulating in digital spaces. This study employs a qualitative case study method to examine how the Indonesian fanbase of Kim Hyun-Joong functions as an integrated crisis communication system in supporting the artist's image recovery process. Data were collected through in-depth interviews with fanbase administrators and active members, supplemented by systematic observation of fanbase accounts on social media platforms including TikTok, Instagram, and Twitter. The findings reveal five interconnected strategic functions performed by the fanbase: information curation, action coordination, opinion building, communication bridging, and digital archiving. These functions form a cohesive, self-sustaining communication ecosystem. Fan resilience, analyzed through Grotberg's framework of I Have, I Am, and I Can, serves as the foundation for consistent, creative, and sustainable digital activities even after the immediate pressure of cancel culture gradually subsided. This research demonstrates that social media is not merely a platform for self-expression but an effective strategic communication tool with real and measurable impact on digital reputation recovery. The study contributes to the expansion of community-based crisis communication theory and participatory culture in the context of the Korean Wave phenomenon.